Spectacular Rubens : the Triumph of the Eucharist ; [... on the occasion of the Exhibition Spectacular Rubens:The Triumph of the Eucharist, on view at the J. Paul Getty Museum at the Getty Center, Los Angeles, from October 14, 2014, to January 11, 2015 and at the Museum of Fine Arts, Houston, from February 15 to May 10, 2015] - Vergara, Alexander; Vergara, Alexander; Rubens, Peter Paul (J. Paul Getty Museum, 2014)
"Presents information about Peter Paul Rubens and his Triumph of the Eucharist series, consisting of modelli (oil paintings on panel) and monumental tapestries. Essays discuss the history and the recent restoration of the panels and tapestries"--